Bacteriophage-mediated biosynthesis of MnO2NPs and MgONPs and their role in the protection of plants from bacterial pathogens - Ogunyemi, Solabomi Olaitan; Abdallah, Yasmine; Ibrahim, Ezzeldin; Zhang, Yang; Bi, Ji’an; Wang, Fang; Ahmed, Temoor; Alkhalifah, Dalal Hussien M.; Hozzein, Wael N.; Yan, Chengqi; Li, Bin; Xu, Lihui (Frontiers in Microbiology, 2023)
Introduction Xanthomonas oryzae pv. oryzae (Xoo) is the plant pathogen of Bacterial Leaf Blight (BLB), which causes yield loss in rice. Methods In this study, the lysate of Xoo bacteriophage X3 was used to mediate the bio-synthesis of MgO and MnO2. The physiochemical features of MgONPs and MnO2NPs were observed via Ultraviolet - Visible spectroscopy (UV–Vis), X-ray diffraction (XRD), Transmission/Scanning electron microscopy (TEM/SEM), Energy dispersive spectrum (EDS), and Fourier-transform infrared spectrum (FTIR). The impact of nanoparticles on plant growth and bacterial leaf blight disease were evaluated. Chlorophyll fluorescence was used to determine whether the nanoparticles application were toxic to the plants. Results An absorption peak of 215 and 230 nm for MgO and MnO2, respectively, confirmed nanoparticle formation via UV–Vis. The crystalline nature of the nanoparticles was detected by the analysis of XRD. Bacteriological tests indicated that MgONPs and MnO2NPs sized 12.5 and 9.8 nm, respectively, had strong in vitro antibacterial effects on rice bacterial blight pathogen, Xoo. MnO2NPs were found to have the most significant antagonist effect on nutrient agar plates, while MgONPs had the most significant impact on bacterial growth in nutrient broth and on cellular efflux. Furthermore, no toxicity to plants was observed for MgONPs and MnO2NPs, indeed, MgONPs at 200 μg/mL significantly increased the quantum efficiency of PSII photochemistry on the model plant, Arabidopsis, in light (ΦPSII) compared to other interactions. Additionally, significant suppression of BLB was noted in rice seedlings amended with the synthesized MgONPs and MnO2NPs. MnO2NPs showed promotion of plant growth in the presence of Xoo compared to MgONPs. Conclusion An effective alternative for the biological production of MgONPs and MnO2NPs was reported, which serves as an effective substitute to control plant bacterial disease with no phytotoxic effect.